Penggunaan Media Video pada Pembelajaran Jarak Jauh Pendidikan Agama Islam di SMP Negeri 2 Wonomulyo, Kabupaten Polewali Mandar - Sudirman; Muslimin; Anis Kharimatunisa (IAI DDI POLEWALI MANDAR, 2022)
The main problems in this study are: (1) How to use video media in the distance learning Islamic education subjects at SMP Negeri 2 Wonomulyo, Polewali Mandar Regency? (2) What are the supporting and inhibiting factors in using Video Media in the distance learning Islamic Education at SMP Negeri 2 Wonomulyo Polewali Mandar Regency? This type of research is qualitative research that builds meaning based on data in the field. This qualitative research procedure pro duces descriptive data in the form of written or spoken words from people and observable behavior. Data were collected by conducting observations, in - depth interviews, and documentation. Data analysis is carried out by giving meaning to the collected data, and conclusions are drawn from that data. The indicators of success in this study are: (1) To determine the use of video media in the distance learning Islamic Religious Education subjects at SMP Negeri 2 Wonomulyo, Polewali Mandar Regency, (2) To know th e supporting and inhibiting factors in the use of video media in distance learning. Islamic Religious Education lessons at SMP Negeri 2 Wonomulyo, Polewali Mandar Regency. The results of observations from the application of the use of distance learning vid eo media to the subjects of Islamic Education at SMP Negeri 2 Wonomulyo Polewali Mandar District found that the use of learning media in the era of globalization which has developed rapidly in information and communication technology is very interesting to use in learning, namely video media. With the use of media, learning becomes more interesting with various learning media, making students motivated to listen to knowledge. This case shows that video media can stimulate teachers' creativity, interest, and motivation to prepare for learning.